Morphological investigation of tissues following experimental mine-blast trauma. - Kovalov, G. A.; Chizh, N. A.; Volina, V. V.; Belochkina, I. V.; Mikhailova, I. P.; Musatova, I. B. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Development and improvement of methods of treating patients with a mine-blast trauma (MBT) involves the experiments with animals. A particular way to simulate MBT in vivo determines the nature and range of the injury severity as well as their possible regulation. Objective. Morphological evaluation of the severity of rat femoral tissue injuries following MBT depending on the powder charge energy and availability of strike elements. Methods. The MBT modelling was done with cartridge-operated guns. The inflicted wounds were histologically studied at the 7th day following injury. Preparations were stained with hematoxylin and eosin. Results. Duration of the inflammative stage was determined by the extent of tissue injury. When using charges of high and medium energies morphological evidence of simultaneous occurrence of the inflammative and regenerative stages became evident. Application of a low energy charge resulted in predomination of the regenerative stage symptoms manifesting themselves as a dense layer of horizontally oriented fibroblasts and considerable amount of collagen fibres in the upper departments of the maturing granulation tissue. An increased amount of the newly formed vessels became also evident. Necrotic tissue free zones demonstrated transition to the formation of the muscular-connective graft. Conclusion. The extent of tissue injury following MBT in the in vivo experiments is determined by the energy value of a powder charge and availability of strike elements, the energy value being decisive. Simulation of MBT with a pre-determined extent of injury allows for specifying a standard range of injuries, required for development of new approaches for treating the above traumas.